States of consciousness experimental insights into meditation, waking, sleep and dreams - Cvetkovic, Dean; Cosic, I. (Irena) 1952- (The Frontiers collection, 2011)
In this accessible overview of current knowledge, an expert team of editors and authors describe experimental approaches to consciousness. These approaches are shedding light on some of the hitherto unknown aspects of the distinct states of human consciousness, including the waking state, different states of sleep and dreaming, meditation and more. The book presents the latest research studies by the contributing authors, whose specialities span neuroscience, neurology, biomedical engineering, clinical psychology and psychophysiology, psychosocial medicine and anthropology. Overall this anthology provides the reader with a clear picture of how different states of consciousness can be defined, experimentally measured and analysed. A future byproduct of this knowledge may be anticipated in the development of systematic corrective treatments for many disorders and pathological problems of conscious